An Analysis of the Online Gambling Phenomenon Among the Lower-Middle-Class Society - Irfansyah, Muhammad Fachri; Fu'adi, Tsabut Hasan; Prayogo, Bayu Aji; Setiyaningsih, Sri Isnani (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to understand the phenomenon of the large number of online gamblers among the lower-middle class. The method used in this study is a qualitative case study with data collection techniques in the form of published news media or journals. Data was collected by selecting topics of discussion with similar themes, then grouping the relevant data to be used as research material. The results of this study indicate that individuals engage in online gambling when they are in poor financial and social conditions. In addition, the ease of access to technology encourages people to engage in negative behavior, which in turn causes various impacts and problems to arise, requiring us to take appropriate measures to address the issue of online gambling.